Effectiveness of short-term heat acclimation for highly trained athletes - Garrett, A. T.; Creasy, R.; Rehrer, N. J.; Patterson, M. J.; Cotter, J. D. (European Journal of Applied Physiology, 2012)
Effectiveness of short-term acclimation has generally been undertaken using untrained and moderately-trained participants. The purpose of this study was to determine the impact of short-term (5-day) heat acclimation on highly trained athletes. Eight males (mean ± SD age 21.8 ± 2.1 years, mass 75.2 ± 4.6 kg, [VO2peak 4.9 ± 0.2 L/min and power output 400 ± 27 W) were heat acclimated under controlled hyperthermia (rectal temperature 38.5°C), for 90-min on five consecutive days (T a = 39.5°C, 60% relative humidity). Acclimation was undertaken with dehydration (no fluid-intake) during daily bouts. Participants completed a rowing-specific, heat stress test (HST) 1 day before and after acclimation (T a = 35°C, 60% relative humidity). HST consisted 10-min rowing at 30% peak power output (PPO), 10 min at 60% PPO and 5-min rest before a 2-km performance test, without feedback cues. Participants received 250 mL fluid (4% carbohydrate; osmolality 240-270 mmol/kg) before the HST. Body mass loss during acclimation bouts was 1.6 ± 0.3 kg (2.1%) on day 1 and 2.3 ± 0.4 kg (3.0%) on day 5. In contrast, resting plasma volume increased by 4.5 ± 4.5% from day 1 to 5 (estimated from [Hb] & Hct). Plasma aldosterone increased at rest (52.6 pg m/L; p = 0.03) and end-exercise (162.4 pg m/L; p = 0.00) from day 1 to 5 acclimation. During the HST T re and f c were lowered 0.3°C (p = 0.00) and 14 b min-1 (p = 0.00) after 20-min exercise. The 2-km performance time (6.52.7 min) improved by 4 s (p = 0.00). Meaningful physiological and performance improvements occurred for highly trained athletes using a short-term (5-day) heat acclimation under hyperthermia control, with dehydration.